Meningkatkan Hasil Belajar Menyimak Siswa Menggunakan Media Audiovisual pada Pelajaran Bahasa Indonesia di Kelas II SD Negeri 1 Parerejo, Pringsewu - Jodi Sofyan Efendi; Andri Wicaksono; Hendra Saputra (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2022)
We often encounter in learning Indonesian, especially listening skills, which are often considered boring by students. This happened due to several factors, namely factors originating from students which included a lack of student interest in listening. Meanwhile, other factors come from learning media which are still monotonous and also have an impact on student learning outcomes. In the interview that the writer conducted with the 2nd grade teacher at SD Negeri 1 Parerejo, the writer found that the student learning outcomes were still low with an average score of 64.07 with 15 students who achieved mastery learning with a mastery percentage of 55.56% of the the total number of students totaling 27 students. Thus, the success of listening to students at SD Negeri 1 Parerejo can be said to be still low because there are still many students who have not achieved mastery in learning. There are 12 students who have not achieved listening comprehension mastery with a percentage of 44.44%. Thus, there is a need for improvement to improve students' listening results at SD Negeri 1 Parerejo by implementing learning using aids in the form of learning media.